Developing a Cybersecurity Policy for Low Earth OrbitSatellite Broadband: An International Law Perspective (Global Governance of Low Earth Orbit Satellites, 2025)
The demand for high-speed, low-latency connectivity is driving the rapid deployment of Low Earth Orbit (LEO) satellite constellations (LEOs). The LEOs are becoming integral to global Internet infrastructure to support the increasing need for broadband Internet access for social, economic, and governmental functions. LEOs can significantly reduce the digital divide by reaching underserved regions if utilised effectively. However, the cybersecurity threat landscape expanded by these systems remains a critical concern, with other significant interests—including digital inclusivity, digital autonomy, and data protection—posing obstacles to their effective deployment. Cybersecurity is fundamentally defined as the “security of cyberspace,” which includes the complex web of connections and relationships among entities accessible through a generalized telecommunications network.